O indizível na cena : conteúdo psíquico de vestígios em locais de morte violenta - Cavedon, Barbara Zaffari (2018)
The forensic work on crime scenes focuses primarily on the recognition, study and preservation of traces. From this analysis, it is sought to understand the dynamics of the facts, with the intention of providing subsidies that allow to define aggressors and ways of acting, supporting the criminal investigation. By tradition, the focus of the expert activity in the crime scene is directed to the physical or material vestige. However, in conceiving that the phenomenon of violence has its origin linked to several factors, such as biological, psychological, neurological, social and economic, it is understood that the expression of this phenomenon also occurs in a multiple way. Thus, it is hypothesized, in this research, that there may be a psychic aspect linked to the elements of the violent death scene and that the analysis of this material can qualify the forensic work, bringing benefits to the investigation. Thus, the problem is the following question: in what way is the expression of vestigial psychics in places of violent death? Based on this assumption, and through interdisciplinarity, a bibliographical research is presented on the subjects of expert activity, violence and vestiges linked to the places of death, elaborating the construct of the psychic content. The study also has a bibliographic reference on three types of occurrences that are more propitious to the presence of psychic aspects: suicides, crimes with passionate motivation and crimes related to drug trafficking. The cases attended by the Instituto-Geral de Perícias Department of Criminalistics, linked to 21 police incidents, are showed in order to articulate the bibliographical research and the reality of the expert witnesses carried out in our state, regarding to the possibility of interpreting the psychic content of evidences. The objective of this research was to analyze such content, including its characteristics and the context of its manifestations. It was also sought to verify the similarities of the contents according to the type of fact that caused the attendance and the possible elements to be interpreted from them, such as motivations, characteristics of victims and / or aggressors, premeditation, etc. The research carried out indicated the possibility of expanding the analysis of evidences, also interpreting the psychic aspects of the elements found in places attended by the expert teams. This result indicates that this increase can contribute to the enrichment of expert work and, consequently, to the quality of criminal investigation.